FDG PET/MRI Findings Pointing Toward a Gayet-Wernicke Encephalopathy. (July 2019) - Rozenblum, Laura; Habert, Marie-Odile; Pyatigorskaya, Nadya; Roue-Jagot, Carole; Kas, Aurélie
Abstract : Abstract: We report a case of Gayet-Wernicke encephalopathy, revealed by an 18 F-FDG PET/MRI performed in a patient with memory impairment. Metabolism showed no pattern of neurodegenerative disease, but a severe decrease in hippocampus and mammillary bodies (MBs). MRI images analyzed in light of PET findings revealed MB atrophy coupled with signal-intensity alterations, suggestive of a Gayet-Wernicke encephalopathy. Patient was known for alcohol use disorders, and all previous MRI scans were considered as inconclusive. Symptoms improved with correction of thiamine (vitamin B1 ) deficiency. This report highlights ability of hybrid PET/MRI to investigate small neuronal structures, such as the MBs involved in Gayet-Wernicke disease.